Predictors of heart failure in patients with major beta-thalassemia - Ionut Stanca; Mihaela Rus; Alice Albu; Simona Fica (Technium Social Sciences Journal, 2020)
Cardiomyopathy by loading the myocardium with iron is the cause of heart failure in patients with major beta-thalassemia. In these patients, cardiac systolic function remains normal for a long time, but when signs of heart failure appear, death may occur in the first year, so it is necessary to identify parameters to predict the patient’s progress and prognosis. Materials and methods. We enrolled 62 patients with beta-thalassemia major (30 men and 32 women), mean age 29.9 ± 7.3 years. 32.2% of patients had disorders of carbohydrate metabolism, 12.9% associated hypothyroidism, and the mean ferritin was 1060.9 ± 856.6 ng / ml. Patients were evaluated echocardiographically, using tissue doppler technique to assess systolic and diastolic function. Myocardial mass was calculated using standard formulas and the type of left ventricular remodeling (LV) was thus obtained. Depending on the ferritin level, choosing the threshold value of 1000ng / ml, a group subanalysis of the ultrasound parameters of cardiac systolic and diastolic function was performed. Results. All patients had LV ejection fraction above 50% (LVEF), but longitudinal LV systolic dysfunction was observed in 19.3% of patients. Also in patients with serum ferritin values ??above 1000ng / ml, the parameters of longitudinal systolic function of LV are affected, paradoxically the average value of LVEF being higher in these patients. About a quarter of patients had diastolic dysfunction, but 40.3% had elevated LV filling pressures. We noticed that the batch with ferritin over 1000 ng / ml associated increased LV filling pressures. The evaluation of the function of the right ventricle by tissue Doppler (S wave at the level of the free wall VD) was statistically significantly correlated with the hemoglobin value and we obtained pathological values ??(S VD <11.5 cm / s) especially in the group with ferritin over 1000ng / ml. We noticed the presence of morphological abnormalities of LV, by increasing myocardial mass and the appearance of LV remodeling, 31% of patients showed severe forms, especially eccentric remodeling. It was observed that there is a risk of negative remodeling of the left ventricle in the group of those with ferritin above 1000ng / ml. Conclusions. The study proves that the evaluation of the systolic and diastolic function of the left and right ventricle by tissue Doppler ultrasound is much more accurate in the early detection of myocardial dysfunction. Ferritin levels above 1000ng / ml have been associated with impaired cardiac function parameters. Also, the remodeling of the left ventricle observed in this group of patients may be the first sign of heart failure.